2011
DOI: 10.1007/s00540-011-1186-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propofol and pentobarbital on calcium concentration in presynaptic boutons on a rat hippocampal neuron

Abstract: Propofol and pentobarbital may affect neurotransmitter release from the excitatory presynaptic nerve terminals due to inhibition of increase in [Ca(2+)](pre).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In other hand, it is well known that barbituric anesthetics such as thiopental shows GABA A agonist effects on both nerve and synapses [36,37], however, previous report shows evidences that at this level of barbituric anesthesia in rats (absence of nocifencive reflexes but stable blood pressure and cardiopulmonary rhythms) did not changed the discharge pattern and neuronal functional connectivity evaluated by by auto-and cross-correlation in the spinal dorsal horn when compared to unanaesthetized, decerebrated, spinalized rats [18].…”
Section: Discussionmentioning
confidence: 99%
“…In other hand, it is well known that barbituric anesthetics such as thiopental shows GABA A agonist effects on both nerve and synapses [36,37], however, previous report shows evidences that at this level of barbituric anesthesia in rats (absence of nocifencive reflexes but stable blood pressure and cardiopulmonary rhythms) did not changed the discharge pattern and neuronal functional connectivity evaluated by by auto-and cross-correlation in the spinal dorsal horn when compared to unanaesthetized, decerebrated, spinalized rats [18].…”
Section: Discussionmentioning
confidence: 99%
“…influx (Kozinn et al 2006). Previous reports also demonstrated that propofol selectively inhibits calcium entry through the L-type channel in hippocampal neurons and other cells (Sung et al 2005;Ito et al 2011). Considering the role of Ca 2?…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal CA1 pyramidal neurons were dissociated from 10 -14 day-old Sprague-Dawley rats as previously described [8]. Briefly, the brain was quickly cut into slices of 400-µm thickness using a microslicer (DTK-3000W; Dosaka EM, Kyoto, Japan).…”
Section: Mechanical Dissociation Of Hippocampal Ca1 Neuronsmentioning
confidence: 99%
“…For disassociation, the slices were placed in a chamber containing standard external solution (500 µl, see description below), and the hippocampal CA1 region was contacted with a fire-polished glass pipette. The pipette was mechanically vibrated horizontally for 1 min using a custom-made device, which caused dissociation of pyramidal neurons along with the attached presynaptic boutons [8] [19].…”
Section: Mechanical Dissociation Of Hippocampal Ca1 Neuronsmentioning
confidence: 99%
See 1 more Smart Citation